Design and search for prospective diuretics (CA II Inhibitors) among aroylhydrazones of esters quinone oxime using in silico and in vivo methodology - K.V. Sokolova; V.V. Stavytskyi; S.О. Konovalova; O.A. Podpletnya; S.I. Kovalenko; A.P. Avdeenko (Medičnì Perspektivi, 2022)
The design and search for new selective inhibitors of CA II with a better pharmacological profile, which would cause minimal electrolyte disturbances in the body, remains an urgent problem of medical chemistry and pharmacology today. It is important that the discovered new classes of inhibitors do not always contain the main “pharmacophoric” function (sulfamide), which is characteristic of “classic” drugs (Acetazolamide, Methazolamide, Ethoxzolamide, Dorzolamide and others), but are derivatives of phenols, polyamines, coumarins/thiocoumarins, ureas, thioureas, hydroxamates, etc. These molecules also bind in the active site of the enzyme, but do not interact directly with the catalytic zinc ion or interact through zinc-coordinated water molecules/hydroxide ion. However, this leads to an increase in their selectivity and, as a result, pharmacological action. Continuing the search for compounds that affect urination, we were interested in aroylhydrazones of esters of quinone oxime. Firstly, they are characterized by certain structural features (dynamic and geometric isomerism); secondly, they exhibit redox properties; thirdly, the presence of aromatic fragments makes it possible to create a voluminous combinatorial library for analysis. These compounds are ligands in complexation reactions, and an additional increase in the number of hydrogen acceptors in the molecule due to structural modification will improve ligand-enzymatic interactions with carbonic anhydrase (CAII) and, as a result, reveal new promising diuretics. The aim – design and search for potential diuretics (CA II inhibitors) among aroylhydrazones of esters of quinone oxime using in silico, traditional synthesis and in vivo methodologies. Methods of organic synthesis, physico-chemical methods of analysis of organic compounds (NMR 1H-spectroscopy, elemental analysis). Prediction of affinity to the biological target, prediction of toxicity and lipophilicity of the combinatorial library of benzohydrazides O-aroyl esters of quinone oxime using computer services. The study of compounds affecting the excretory function of rat kidneys was carried out according to the generally accepted method of E.B.Berkhin with water load. The investigation of the probable mechanism was carried out using flexible molecular docking, as an approach to search for molecules that have affinity for human carbonic anhydrase type II (CA II). Macromolecular data of the crystal structure of CA II (PDB ID – 3HS4) were downloaded from the Protein Data Bank (PDB). The design was developed and the search for diuretic agents among benzohydrazides of O-aroyl esters of quinone oximes was developed using in silico methods (prediction of affinity, lipophilicity, toxicity and enzyme-ligand interactions), traditional organic synthesis, and in vivo methods (effect on excretory function of rat kidneys). The synthesis of benzohydrazides of O-aroyl esters of quinone oxime was carried out by the interaction of aroylhydrazines with 4-[(aroylimino)]cyclohexa-2,5-dien-1-ones. The structure of the synthesized compounds was confirmed by elemental analysis and 1H NMR spectra. Studies of the effect of synthesized compounds on the excretory function of rat kidneys allowed us to identify a number of promising compounds among aroylhydrazones of quinonexime esters, which increase daily diuresis by 54.2-352.8% compared to the control group. At the same time, it was established that the most active was N'-(4-[(2-chlorobenzoyloxy)imino]cyclohexa-2,5-dien-1-ylidene)-3-nitrobenzohydrazide, which increased daily diuresis by 352.8% in comparison with the control group, while exceeding the effect of “Hydrochlorothiazide” (170.8%). The developed and implemented strategy for the search for diuretics among benzohydrazides of O-aroylesters of quinone oxime allowed the identification of an effective compound, which in terms of diuretic effect exceeds the comparison drug “Hydrochlorothiazide”. Visualization of the molecular docking of the active compounds showed that their geometry makes it difficult to place them in the pocket of the active site of CA II, but the pronounced diuretic effect can also be associated with their ability to form coordination bonds with the zinc cation. The obtained results justify the further targeted search for potential diuretics among this class of compounds for a more detailed understanding and study of the mechanism of action.